Co-infection with Bartonella bacilliformis and Mycobacterium spp. in a coastal region of Peru - Silva-Caso W. (2017)
Objective: This study investigated an outbreak of Bartonellosis in a coastal region in Peru.Results: A total of 70 (n = 70) samples with clinical criteria for the acute phase of Bartonellosis and a positive peripheral blood smear were included. 22.85% (n = 16) cases of the samples were positive for Bartonella bacilliformis by PCR and automatic sequencing. Of those positive samples, 62.5% (n = 10) cases were positive only for B. bacilliformis and 37.5% (n = 6) cases were positive to both Mycobacterium spp. and B. bacilliformis. The symptom frequencies were similar in patients diagnosed with Carrion's disease and those co-infected with Mycobacterium spp. The most common symptoms were headaches, followed by malaise and arthralgia.